PENGARUH ROA, DER, CR, INFLASI DAN KURS TERHADAP RETURN SAHAM (STUDI KASUS INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2008-2012) - Johannes .; Meri Arisandi (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
ABSTRACT The objectives of this research is to analyze the influence of Return On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), inflation and exchange rate to the stock return of Food and Baverage industry that listed on Indonesian Stock Exchange in the period of 2008-2012.The number of population are 19 companies but the elligable unit to be sample is 16 companies. Analyze technique to describe the varibles relationships used Multiple Linier Regression. Based on the data processing, it is known that simmultaneously the effect of independent variables are significant. Furthermore, partially it is known that the effect of Return On Asset (ROA), inflation, and exchange rate variables are significant, otherwise varieables Debt to Equity Ratio (DER) and Current Ratio (CR) have insignificant effect. Keywords : On Asset (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Inflation, exchange rate, stock return